Multi-objective optimization of intensified processes for the purification of levulinic acid involving economic and environmental objectives - Alcocer-García, Heriberto; Segovia-Hernández, Juan Gabriel; Prado-Rubio, Oscar Andrés; Sánchez-Ramírez, Eduardo; Quiroz-Ramírez, Juan José (Chemical engineering and processing, 2019)
[Display omitted] •Design and optimization of hybrid alternatives to purify levulinc acid.•Multi-objective optimization process considering economic and environmental issues.•Effective downstream processing of levulinic coming from fermentation. Levulinic acid obtained from acid hydrolysis of lignocellulosic biomass is considered within the twelve main chemicals from biomass in terms of economic potential due to its large number of applications. As product of hydrolysis is obtained a quite diluted stream which contains a lot of water. Consequently, the processing cost is high and it has limitations for further scaling up at industrial level using conventional separation schemes. In the downstream process proposed in this work, initially the water content is removed using a liquid-liquid extractive column, then it is purified by means of a distillation columns-based process. Recently, a set of separation designs has been implemented, including the use of decanters and intensified columns, which has reduced the cost of the process. However, these studies have only focused on optimizing the total annual cost, losing sight of the environmental impact of the process. In addition, some improvements may be applied from the process intensification point of view either by thermally couplings or considering a single or multiple walls in a column. Therefore, in this work four LA purification designs are studied, a conventional distillation sequence, a dividing wall column arrangement and a decanter, a dividing wall column configuration with a decanter and thermal coupling, and two dividing wall column and decanter. Those schemes were designed and optimized under a rigorous optimization process by means of a multi-objective hybrid algorithm, differential evolution with tabu list considering two objectives: 1) the total annual cost as the economic criterion and 2) the eco-indicator 99 as the environmental index. The results indicated that the intensified design (using a single dividing wall column) presents better results, with economic savings about 8.42% and a decrease in 10.94% the Eco-indicator 99 in comparison with the optimal conventional sequence.